'We are not the ones to blame'. Gamblers' and providers' appraisal of self-exclusion in Germany - Ludwig Kraus; Andreas Bickl; Lucia Sedlacek; Larissa Schwarzkopf; Jenny Cisneros Örnberg; Johanna K. Loy (BMC, 2023)
Abstract Background Given low utilization by individuals experiencing gambling problems the potential of self-exclusion (SE) might be not fully exploited in Germany. This paper aims to gain insight into different actors' perceptions and reflections on the problems and difficulties in the process of self-exclusion to delineate which specific attitudes hamper a successful implementation of SE. Methods 13 individual and four group interviews with individuals experiencing gambling problems and governmental or commercial gambling providers were examined. A Grounded Theory Approach was used to portray the opinions of these different actors on existing regulations of SE and to delineate potentially diverging interests between the distinct groups. Results The interviewees agreed on the usefulness of SE and consented that it is important to early recognize individuals experiencing gambling problems. They also considered the present practice insufficient but for different reasons. Individuals experiencing gambling problems and providers particularly disagreed on addressing individuals experiencing gambling problems. While individuals experiencing gambling problems stated that they had hardly ever been approached, providers argued that help offers were mostly rejected. Especially commercial providers also regarded insufficient German language skills and rapid fluctuation of guests as strong barriers to approaching individuals experiencing gambling problems. Interviewees from governmental venues furthermore suspected that commercial providers took addressing individuals experiencing gambling problems less seriously. Conclusion Our results emphasize the dilemma of conflicting interests in both individuals experiencing gambling problems and providers. Rather than acting against the economic interests of employers, venue staff blame individuals experiencing gambling problems for lack of problem recognition. Conversely, individuals experiencing gambling problems blame the providers for not offering help. To address individuals experiencing gambling problems appropriate staff training is required, and SE regulations need to be controlled by an independent body rather than by the providers themselves.